RELATIONSHIP BETWEEN DEGREE OF STRESS AND PHYSICAL ACTIVITY OF FEMALE STUDENTS WITH PREMENSTRUAL SYNDROME - Rina Wahyu Andani (Universitas Airlangga, 2020)
Background: Premenstrual syndrome (PMS) is a group of symptoms consisting of physical, psychological, and behavioral disorders that can occur in women before menstruation and can be triggered or aggravated by factors such as their degree of stress and physical activity. Purpose: This research aimed to analyze the relationship between degree of stress and physical activity and premenstrual syndrome occurrence in female students. Method: This study used analytical observational research with a cross-sectional research design. Female students of the S1 Public Health class of 2016-2019 were used as the sample (n = 93) in this research. Sampling was conducted via the simple random sampling technique. A bivariate analysis was conducted using chi-square testing. The research was conducted between August and September of 2019 at the Faculty of Public Health, Universitas Airlangga. Results: Severe to extreme symptoms felt most often by respondents were muscle and joint pain, abdominal pain, and irritability. The prevalence of premenstrual syndrome with moderate to severe symptoms in female students of the S1 Public Health class was 46.24% and the prevalence of stressed female students was 70.97%. Statistical test results showed a relationship between the degree of stress and premenstrual syndrome occurrence (p = 0.01) and a relationship between physical activity and premenstrual syndrome occurrence (p = 0.04). Statistical tests also showed no relationship between the age of menarche and premenstrual syndrome occurrence (p = 0.50). Conclusion: There was a significant relationship between degree of stress and physical activity and premenstrual syndrome occurrence.